"We can hardly even do it nowadays. So, what's going to happen in 5 years from now, 10 years from now?" The health and community care and support needs and preferences of older people living with HIV in Ontario, Canada: a qualitative study. (29th September 2022) - Murzin, Kate; Racz, Elizabeth; Behrens, D. M.; Conway, Tracey; Da Silva, George; Fitzpatrick, Eimear; Lindsay, Joanne D.; Walmsley, Sharon L.; ,
Abstract: Introduction: The population of people living with HIV (PLWH) is ageing consequent to effective treatment and a steady stream of new diagnoses among older adults. PLWH experience a greater burden of age‐related comorbidities and poorer social determinants of health compared to their HIV‐negative peers, yet comprehensive requisites for care and support as PLWH age remain poorly understood. Preferences And Needs for Ageing Care among HIV‐positive Elderly people in Ontario, Canada (PANACHE ON), explored the health and community care and social support needs and preferences of a diverse group of older PLWH (age 60+) and described life course experiences among older PLWH that shape these needs and preferences and whether they are met. Methods: PANACHE ON was a qualitative community‐based participatory research study. In‐person focus groups using a semi‐structured interview guide were co‐facilitated by pairs of trained older PLWH from July to October 2019. Purposive sampling bolstered the inclusion of communities disproportionately affected by HIV in Ontario. Descriptive analysis was used to summarize demographic data; participatory data analysis was conducted by a subset of the research team, with transcripts double‐coded and analysed using NVIVO 12 Plus. Results: A total of 73 PLWH participated, 66% identified as men. The mean age was 64 years (range 55–77) and median time living with HIV was 23 years (range 2–37). The current and anticipated needs of older PLWH, many of which were only partially met, included necessities such as food and housing, mobility and sensory aids, in‐home support, social and emotional support, transportation and information. Three experiences—trauma, stigma and uncertainty—intersected in the lives of many of our participants, shaping their needs for care and support, and impacting the ease with which these needs were met. Conclusions: Unmet health and social needs and limited control over the availability and accessibility of ageing‐related care and support due to resource constraints or reduced capacity for self‐advocacy results in anxiety about the future among older PLWH, despite their well‐developed coping strategies and experience navigating systems of care. These study findings will inform the development of the first national needs assessment of older PLWH in Canada.